Method of manufacturing a separator for a rechargeable battery, separator for a rechargeable battery, and rechargeable battery
Patent Information
- Application Number
- CN202610548296.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-30
- Filing Date
- 2026-04-23
- Publication Date
- 2026-10-30
Smart Images

Figure CN123018340A_ABST
Abstract
Description
[0001] This application claims priority and benefit to Korean Patent Application No. 10-2025-0057450, filed on April 30, 2025, with the Korean Intellectual Property Office, the entire disclosure of which is incorporated herein by reference. Technical Field
[0002] This disclosure relates to a method for manufacturing a separator for a rechargeable battery, the separator for a rechargeable battery, and a rechargeable battery. Background Technology
[0003] With the increasing prevalence of battery-powered electronic devices (such as mobile phones, laptops, and electric vehicles), the demand for rechargeable batteries with high energy density and high capacity is growing. Therefore, improving the performance of rechargeable lithium batteries could be advantageous.
[0004] Rechargeable lithium batteries typically include positive and negative electrodes containing active materials capable of inserting and deintercalating lithium ions, and generate electrical energy through oxidation and reduction reactions when lithium ions are deintercalated from the positive electrode and inserted into the negative electrode or deintercalated from the negative electrode and inserted into the positive electrode.
[0005] Rechargeable lithium batteries may include a separator between the positive and negative electrodes. Summary of the Invention
[0006] This disclosure relates to a separator for a rechargeable battery, the separator comprising a coating having a small average pore size and high porosity.
[0007] This disclosure also relates to a separator for rechargeable batteries, the separator having phase separation between the binder and the filler.
[0008] According to one aspect of this disclosure, a method for manufacturing a separator for a rechargeable battery is provided.
[0009] A method for manufacturing a separator for a rechargeable battery includes the steps of: coating a composition comprising a binder, a solvent, and a filler onto at least one surface of a porous substrate to form a coated film for the coated layer; and drying the coated film for the coated layer to manufacture a separator for a rechargeable battery. The drying includes drying the coated film for the coated layer in a first drying zone, and the first drying zone has a dew point in the range of about 10°C to about 25°C and a relative humidity in the range of about 20% to about 70%.
[0010] According to another aspect of this disclosure, a separator for a rechargeable battery is provided.
[0011] The separator for a rechargeable battery includes a porous substrate and a coating layer laminated on at least one surface of the porous substrate, wherein the coating layer includes a binder and a filler and has an average pore size greater than about 10 nm and about 50 nm or less (e.g., an average pore size greater than about 20 nm and about 40 nm or less).
[0012] According to another aspect of this disclosure, a rechargeable battery is provided.
[0013] A rechargeable battery includes a positive electrode, a negative electrode, and the aforementioned separator for a rechargeable battery located between the positive and negative electrodes. Attached Figure Description
[0014] The above and other objects, features, and advantages of this disclosure will become more apparent to those skilled in the art from the detailed description of exemplary embodiments with reference to the accompanying drawings, in which: Figure 1 This is a conceptual diagram of the coating layer of the diaphragm based on the coating layer preparation method; Figure 2 This illustrates phase separation between the binder and filler in a coated film used as a coating layer in a diaphragm manufacturing process; Figure 3 This is a cross-sectional view of a separator for a rechargeable battery according to an example embodiment; Figures 4 to 7 This is a schematic diagram illustrating a rechargeable lithium battery according to an example embodiment; Figure 8 The scanning electron microscope (SEM) results of the coating layer of the diaphragm in Example 1 are shown. Figure 9 SEM results of the coating of the diaphragm in Comparative Example 4 are shown; and Figure 10 This is a flowchart illustrating a method for manufacturing a separator for a rechargeable battery according to an example embodiment. Detailed Implementation
[0015] Example embodiments of the present disclosure are described in detail below. However, these example embodiments are provided by way of illustration, and the present disclosure is not limited thereto, and is limited only by the scope of the appended claims.
[0016] In the following, exemplary embodiments of the present disclosure are described in detail with reference to the accompanying drawings. The terms or words used in this specification and claims should not be construed as limited to their typical or dictionary meanings, but should be interpreted in accordance with the meaning and concept consistent with the technical spirit of the present disclosure. Therefore, it should be understood that the exemplary embodiments described in this specification and the constructions shown in the accompanying drawings are only some of the exemplary embodiments of the present disclosure and do not represent the entirety of the technical spirit of the present disclosure; various equivalents and modifications may exist at the time of filing this application. Furthermore, when the terms "comprising" and "including" and / or variations thereof are used in this specification, it indicates the presence of the mentioned shapes, quantities, steps, operations, elements, components, and / or groups thereof, and does not exclude the presence or addition of one or more other shapes, quantities, operations, elements, components, and / or groups. Additionally, when describing exemplary embodiments of the present disclosure, the phrase "may be" may include "one or more exemplary embodiments of the present disclosure."
[0017] Furthermore, to aid in understanding the disclosure, the accompanying drawings may not be drawn to scale, and the dimensions of some components may be exaggerated. Additionally, the same reference numerals may be assigned to the same components in different embodiments.
[0018] Unless otherwise stated herein, when a component such as a layer, film, region, plate, etc., is described as being “on” another component, it includes not only the case where the component is “directly on” the other component, but also the case where there is another component in between.
[0019] Unless otherwise stated in this specification, anything indicated in the singular may also include the plural. Furthermore, unless otherwise stated, “A or B” may mean “including A, including B, or including both A and B”.
[0020] As used herein, the term "combination of them" may mean mixtures, laminates, complexes, copolymers, alloys, blends, and reaction products of the components.
[0021] Here, the term "particle size D50" refers to the average particle size, which means the diameter of the particles that constitute 50% of the cumulative volume in the particle size distribution. Particle size distribution can be measured by methods known to those skilled in the art. For example, particle size distribution can be measured using, for example, a particle size analyzer, transmission electron microscopy, or scanning electron microscopy. In another method, the D50 value can be obtained by measuring the particle size using, for example, a measuring device utilizing dynamic light scattering, performing data analysis to count the number of particles for each particle size range, and then calculating the particle size from that. Alternatively, D50 can be measured using laser diffraction. For example, when measured by laser diffraction, after dispersing the particles to be measured in a dispersion medium, the particles can be introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) and irradiated with ultrasound at approximately 28 kHz at an output of 60 W, and the D50 based on 50% of the particle size distribution in the measuring device can be calculated.
[0022] When the terms “about” or “substantially” are used in conjunction with numerical values in this specification, it means that the relevant numerical value includes a tolerance of ±10% around the stated value. When a range is specified, the range includes all values within that range, such as increments of 0.1%.
[0023] According to one example embodiment, a method for manufacturing a separator for a rechargeable battery, a separator for a rechargeable battery, and a rechargeable battery are provided.
[0024] According to one example embodiment, the separator for a rechargeable battery can be used in a rechargeable lithium battery. However, this disclosure is not limited thereto, and in addition to rechargeable lithium batteries, the separator can also be applied to rechargeable metal batteries, such as rechargeable sodium batteries.
[0025] According to one example embodiment, a method for manufacturing a separator for a rechargeable battery includes the steps of: coating a composition comprising a binder, a solvent, and a filler onto at least one surface of a porous substrate to form a coated film for the coated layer; and drying the coated film for the coated layer to manufacture a separator for a rechargeable battery. For example, the drying includes drying the coated film for the coated layer in a first drying zone, and the first drying zone has a dew point in the range of about 10°C to about 25°C and a relative humidity in the range of about 20% to about 70%.
[0026] The manufacturing method can produce a separator for a rechargeable battery, the separator comprising a porous substrate and a coating layer formed on at least one surface of the porous substrate, wherein the coating layer comprises a binder and a filler and has a small average pore size and a high porosity, and the binder and filler are phase-separated in the coating layer.
[0027] Reference Figure 1 Describe the average pore size and porosity.
[0028] Figure 1 (A) is a conceptual diagram of a coating layer for a separator used in a rechargeable battery that has not been manufactured by the above-described manufacturing method. Figure 1 (B) is a conceptual diagram of a coating layer for a separator used in a rechargeable battery, manufactured by the above-described manufacturing method.
[0029] Reference Figure 1 , Figure 1 (A) and (B) in the figure show that pores II are distributed in the matrix I of the coating layer. Figure 1 (A) shows that pore II has a large size and low porosity, while Figure 1 (B) in the diagram shows that pore II has a small size and high porosity.
[0030] According to one example embodiment, the manufacturing method can produce a separator for a rechargeable battery, the separator comprising, as shown in the example embodiment... Figure 1 The coating shown in (B) has a small pore size (correspondingly, a small average pore size) and high porosity. When the pore size and porosity in the coating are small, it provides the effect of improving the permeability of the separator and reducing the membrane resistance, thus enhancing the safety of the battery.
[0031] In this specification, "pore size" can be determined by measuring the coating using an advanced capillary flow porosity measurement method (e.g., the PMI method) via a pore size analyzer (porosity meter) to determine the through-hole characteristics, including the pore size distribution.
[0032] In this specification, the "average pore size" can be determined by measuring the coating using the PMI method.
[0033] In this specification, "porosity" can be determined by measuring the coating using the PMI method.
[0034] The PMI measurement method is as follows: 1) Install the fittings for measuring the adhesive on the device.
[0035] 2) Turn on the device and PC (for the device, set the power switch to On).
[0036] 3) Open the valve on the nitrogen pipeline at the back of the equipment to supply nitrogen into the equipment (appropriate pressure: 0.15MPa).
[0037] 4) Click HorizonMB on your PC to run the software, and then allow the device to stabilize (at least 1 hour).
[0038] 5) Before taking measurements, check that the settings are set correctly.
[0039] (Resolution: 8, Scan: 32, Acquisition Mode: Absorbance, Detector Gain: 237.84 ※After selection, check if the signal strength is within the range of 20 to 80).
[0040] 6) With no sample on the sample holder, move the fixing device to the side and press the Reference button to start the measurement.
[0041] 7) Enter the name and storage path of the sample to be measured (sample information).
[0042] 8) Place the sample on the sample holder and press the Measure button to start the measurement.
[0043] 9) After the measurement is completed, obtain the absorbance in the desired region.
[0044] You can select the desired region by choosing Mathematics → Baseline Calculate. For the CF key, enter 995cm. -1 Up to 1330cm -1 Use the range as a baseline, then press the Calculate button to obtain the result based on 995cm. -1 Up to 1330cm -1 A graph showing regional variations. Absorbance values can be viewed by zooming in on the graph and moving the mouse cursor to 1184 cm⁻¹. -1 We'll confirm from the vicinity.
[0045] Next, refer to Figure 2 The description describes the phase separation between the binder and filler in a coating film used for a coating layer in a manufacturing method according to an example embodiment.
[0046] Reference Figure 2 The coating can form a coating film 2a for the coating layer on one surface of the porous substrate 1. The coating film 2a includes an adhesive 5 and a solvent ( Figure 2 (not shown in the image) and packing 3.
[0047] In the coating film 2a used for the coating layer, the binder 5 and the filler 3 can be mixed with each other.
[0048] In one example, the coating film 2a used for the coating layer may include an adhesive 5 that is closer to the porous substrate 1 than the filler 3, and may also include the filler 3 that is farther away from the porous substrate 1 than the adhesive 5. This may be the case when the size of the adhesive 5 is relatively smaller than the size of the filler 3, but this disclosure is not limited thereto.
[0049] Drying the coating film 2a used for coating can transform the coating film 2a into coating layer 2.
[0050] The coating layer 2 includes a filler 3 and a binder 4. A large amount of binder 4 can be located away from the porous substrate 1, while a relatively small amount of binder 4 can be positioned close to the porous substrate 1. In the coating layer 2, since a relatively large amount of binder 4 is located at the surface of the coating layer 2, the binder 4 can be separated from the filler 3. Therefore, the coating layer 2 can have high adhesion to the electrode and prevent or suppress battery deformation during charging and discharging. Furthermore, the coating layer 2 can provide improvements in short-circuit defects and overcharging.
[0051] Figure 2 The illustration shows the case where the binder 5 is in granular form. The binder 5 can be converted into the binder 4 by dissolving it in a solvent. However, this disclosure is not limited thereto.
[0052] The following describes in detail a method for manufacturing a separator for a rechargeable battery according to an example embodiment.
[0053] A composition comprising an adhesive, a solvent, and a filler is applied to at least one surface of a porous substrate to form a coating film for coating.
[0054] Porous substrate Porous substrates can have numerous pores and can be used in typical electrochemical devices. As a non-limiting example, a porous substrate can be or include a polymer membrane formed of or comprising any polymer or copolymer or mixture of two or more of the following: polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetal, polyamide, polyimide, polycarbonate, polyetheretherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, and polytetrafluoroethylene (e.g., Teflon). ® ).
[0055] The porous substrate can be or includes, for example, a polyolefin-based substrate containing polyolefins, and the polyolefin-based substrate can contribute to enhanced battery safety due to its desired or improved shut-off function. The polyolefin-based substrate can be or includes at least one of, for example, polyethylene monolayer membranes, polypropylene monolayer membranes, polyethylene / polypropylene bilayer membranes, polypropylene / polyethylene / polypropylene trilayer membranes, and polyethylene / polypropylene / polyethylene trilayer membranes. Furthermore, the polyolefin-based substrate may include non-olefin resins in addition to olefin resins, or may include copolymers of olefin monomers and non-olefin monomers.
[0056] Porous substrates can have a thickness in the range of about 1 μm to about 40 μm (e.g., 1 μm to 30 μm, 1 μm to 20 μm or 3 μm to 10 μm).
[0057] adhesive Adhesives can hold fillers within a coating layer and simultaneously or concurrently increase the adhesion of the coating layer. According to one example embodiment, the adhesive can be a viscous adhesive.
[0058] Adhesive binders can be or include organic adhesive binders. Here, "organic adhesive binder" can refer to a binder dissolved in an organic solvent. As described below, an organic solvent is used as the solvent in the manufacturing method. Organic adhesive binders can readily dissolve in organic solvents to facilitate phase separation.
[0059] Organic adhesives can be, or include, fluorinated adhesives. Fluorinated adhesives can improve the dry and wet adhesion of membranes.
[0060] Fluorinated adhesives can include those with carboxylic acid or hydroxyl groups. Fluorinated adhesives with carboxylic acid or hydroxyl groups can improve the dry and wet adhesion of membranes.
[0061] Fluorinated adhesives having carboxylic acid groups or hydroxyl groups may include polyvinylidene fluoride (PVDF) adhesives having carboxylic acid groups or hydroxyl groups.
[0062] The PVDF-based binder may include, for example, structural units derived from vinylidene fluoride and structural units derived from monomers having at least one carboxylic acid group or hydroxyl group. Structural units derived from monomers having at least one carboxylic acid group or hydroxyl group can provide improved wet adhesion, durability, and permeability of the membrane. Monomers having at least one carboxylic acid group or hydroxyl group may be or include one or more of (meth)acrylic acid, itaconic acid or derivatives thereof, maleic acid or derivatives thereof, and hydroxyalkyl allyl ethers.
[0063] The PVDF-based adhesive may also include structural units derived from monomers that are copolymerizable with vinylidene fluoride. The copolymerizable monomers may be, or include, at least one of trichloroethylene monomers, chlorotrifluoroethylene monomers, trifluoroethylene monomers, hexafluoropropylene monomers, tetrafluoroethylene monomers, and ethylene monomers.
[0064] According to one example embodiment, the PVDF-type adhesive is or includes a copolymer of vinylidene fluoride, a monomer having a carboxylic acid group or a hydroxyl group, and hexafluoropropylene, and may include structural units derived from vinylidene fluoride, structural units derived from monomers having a carboxylic acid group or a hydroxyl group, and structural units derived from hexafluoropropylene.
[0065] PVDF-based binders containing carboxylic acid or hydroxyl groups can have a glass transition temperature (Tg) in the range of about -70°C to about -20°C and a weight-average molecular weight in the range of about 200,000 g / mol to about 3,000,000 g / mol, 200,000 g / mol to 2,000,000 g / mol, or 300,000 g / mol to 1,500,000 g / mol. Within these ranges, the membrane can exhibit desired or improved adhesion.
[0066] The glass transition temperature can be measured using DSC by typical methods known to those skilled in the art. The weight-average molecular weight can be obtained, for example, by gel permeation chromatography as a polystyrene equivalent.
[0067] According to one example embodiment, the PVDF-based adhesive may comprise repeating units ranging from about 80 mol% to about 99 mol% of vinylidene fluoride repeating units, from about 0.5 mol% to about 10 mol% of hexafluoropropylene repeating units, and from about 0.5 mol% to about 10 mol% of repeating units derived from monomers having carboxylic acid groups or hydroxyl groups.
[0068] The PVDF-based adhesive can take various forms, such as alternating polymers in which repeating units are distributed alternately, random polymers in which repeating units are distributed randomly, and grafted polymers in which some of the repeating units are grafted. Furthermore, the PVDF-based adhesive can be in the form of linear polymers, branched polymers, or mixtures thereof.
[0069] In one example, the PVDF-based adhesive may include vinylidene fluoride repeating units in an amount ranging from about 90 mol% to about 99.5 mol%, 93 mol% to 99 mol%, or 95 mol% to 99 mol%, and hexafluoropropylene repeating units in an amount greater than about 0 mol% and about 10 mol% or less, ranging from about 0.5 mol% to about 10 mol%, 1 mol% to 10 mol%, 1 mol% to 9 mol%, 2 mol% to 7 mol%, or 4 mol% to 6 mol%. Within these ranges, the PVDF-based adhesive can exhibit desired or improved solubility in low-boiling-point solvents, ensuring chemical stability, and possessing desired or improved adhesion. Therefore, an adhesive layer can be formed using low-boiling-point solvents without any additional processes, and the degradation of permeability that may inevitably occur with the use of high-boiling-point solvents can be reduced or prevented. Low-boiling-point solvents are described in detail below.
[0070] PVDF-based adhesives containing carboxylic acid groups or hydroxyl groups can have a crystallinity ranging from about 40% to about 65% (e.g., 45% to 60% or 50% to 55%). In this case, the adhesive can exhibit desired or improved adhesion. The crystallinity of this PVDF-based adhesive is higher than that of fluorinated adhesives without carboxylic acid groups and hydroxyl groups, which will be described below.
[0071] PVDF-based adhesives having carboxylic acid or hydroxyl groups can have a melting point of about 150°C or higher (e.g., in the range of about 150°C to about 200°C).
[0072] Adhesive adhesives are organic adhesive adhesives, and may also include fluorinated adhesive adhesives that do not have carboxylic acid groups and hydroxyl groups. Fluorinated adhesive adhesives that do not have carboxylic acid groups and hydroxyl groups can improve the adhesion of the adhesive layer.
[0073] Fluorinated adhesives that do not have carboxylic acid and hydroxyl groups may include repeating units derived from vinylidene fluoride and repeating units derived from monomers that are copolymerizable with vinylidene fluoride. The copolymerizable monomers may be or include at least one of trichloroethylene monomers, chlorotrifluoroethylene monomers, trifluoroethylene monomers, hexafluoropropylene monomers, tetrafluoroethylene monomers, and ethylene monomers.
[0074] Fluorinated adhesives without carboxylic acid and hydroxyl groups can take various forms (such as alternating polymers, random polymers, and grafted polymers). Fluorinated adhesives without carboxylic acid and hydroxyl groups can be linear polymers, branched polymers, or mixtures thereof, and can be polymers that have more branches than fluorinated adhesives with carboxylic acid and hydroxyl groups.
[0075] Fluorinated adhesives that do not have carboxylic acid groups and hydroxyl groups may include repeating units of vinylidene fluoride and repeating units of hexafluoropropylene.
[0076] Vinylidene fluoride repeating units can be included in the binder in amounts ranging from about 90 mol% to about 99.5 mol%, 93 mol% to 99 mol%, or 95 mol% to 99 mol%. When vinylidene fluoride repeating units are included within these ranges, the binder ensures desired or improved adhesion and electrolyte absorption. Hexafluoropropylene repeating units can be included in the binder in amounts greater than about 0 mol% and about 10 mol% or less, ranging from about 0.5 mol% to about 10 mol%, 1 mol% to 9 mol%, 2 mol% to 8 mol%, 3 mol% to 7 mol%, or 4 mol% to 6 mol%. When hexafluoropropylene repeating units are included within these ranges, the binder ensures chemical stability while exhibiting desired or improved solubility in low-boiling-point solvents and desired or improved adhesion. Therefore, a low-boiling-point solvent can be used to form the adhesive layer without any additional processing, and the degradation of permeability that may inevitably occur when using high-boiling-point solvents can be reduced or prevented.
[0077] Fluorinated adhesives lacking carboxylic acid and hydroxyl groups can have a glass transition temperature (Tg) in the range of about -70°C to about 20°C and a weight-average molecular weight in the range of about 800,000 to about 2,000,000 or 800,000 to 1,900,000. When the weight-average molecular weight falls within the above ranges, adhesive layers including such adhesives can exhibit desired or improved wet and dry adhesion.
[0078] The adhesive may have a crystallinity in the range of about 35% to about 45% (e.g., 35% to 40%). When the adhesive has a crystallinity in the above range, the adhesive layer including the adhesive may exhibit desired or improved dry adhesion. The crystallinity of the adhesive is lower than that of fluorinated adhesives having hydroxyl or carboxylic acid groups.
[0079] Fluorinated adhesives that do not have carboxylic acid and hydroxyl groups may have a melting point of about 150°C or higher (e.g., in the range of about 150°C to about 200°C).
[0080] Both types of binders can be prepared by various known methods (such as emulsion polymerization, suspension polymerization, bulk polymerization and solution polymerization, for example), and can be prepared by emulsion polymerization, for example.
[0081] filler The filler can have an average particle size D50 of about 1.0 μm or less (e.g., about 0.4 μm or less, or in the range of about 0.1 μm to about 0.35 μm). Within this range, the effect of improving heat shrinkage can be achieved.
[0082] The filler may be or includes, for example, inorganic fillers, organic fillers, organic / inorganic composite fillers, or combinations thereof. Inorganic fillers may be or include ceramic materials capable of improving heat resistance. Inorganic fillers may be or include at least one of, for example, metal oxides, quasi-metal oxides, metal fluorides, metal hydroxides, or combinations thereof. Inorganic fillers may include, for example, at least one of, but are not limited to, alumina (Al₂O₃), SiO₂, TiO₂, SnO₂, CeO₂, MgO, NiO, CaO, GaO, ZnO, ZrO₂, Y₂O₃, SrTiO₃, BaTiO₃, Mg(OH)₂, boehmite, or combinations thereof. Organic fillers may include at least one of, but are not limited to, acrylic compounds, imide compounds, amide compounds, or combinations thereof. Organic fillers may have a core-shell structure, but are not limited to this.
[0083] In one example, the filler could be alumina.
[0084] The packing material can be spherical, plate-shaped, cubic, or amorphous. For example, the packing material can be plate-shaped.
[0085] solvent The solvent can be readily applied to at least one surface of a porous substrate by mixing the binder and filler in the composition used for coating.
[0086] In one example, the solvent can be a low-boiling-point solvent. A low-boiling-point solvent can be, for example, a solvent having a boiling point of 100°C or lower. Because low-boiling-point solvents are readily removed by evaporation during drying, an increase in the permeability of the membrane can be prevented or avoided. For example, the solvent can have a boiling point above 0°C and below 100°C (e.g., 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 10°C to 100°C).
[0087] Boiling point is measured by distillation or computer-based laboratory methods.
[0088] Low-boiling-point solvents may be, or include, at least one of the following: acetone, ethanol, methyl ethyl ketone, ethyl isobutyl ketone, tetrahydrofuran, dimethylformaldehyde, cyclohexane, or mixtures thereof, but are not limited thereto.
[0089] Composition for coating layer Compositions used for coatings may include binders, fillers, and solvents.
[0090] In one example, the binder and filler may be included in the composition for the coating layer in a weight ratio of about 1:10 to about 1:50 (e.g., about 1:20 to about 1:50 by weight). Within the above range, phase separation, membrane adhesion, and membrane resistance in the coating layer can be readily improved.
[0091] In one example, the solvent may be included in amounts from 100 parts by weight to 500 parts by weight (e.g., 100 parts by weight, 150 parts by weight, 200 parts by weight, 250 parts by weight, 300 parts by weight, 350 parts by weight, 400 parts by weight, 450 parts by weight, 500 parts by weight, 200 parts by weight to 500 parts by weight) relative to 100 parts by weight of the binder. Within these ranges, the coating layer can have a uniform surface and can readily improve phase separation in the coating layer.
[0092] Formation of coating film for coating layer A coating film for a coating layer can be formed by applying a composition for the coating layer to at least one surface of a porous substrate. Typical methods known to those skilled in the art can be used in this application. For example, coating can be performed by molding, but is not limited thereto.
[0093] The coating film used for the coating layer can have a thickness of 1 μm to 20 μm (e.g., 1 μm to 10 μm or 1 μm to 3 μm). Within the above range, the thickness of the coating layer, which will be described below, can be easily achieved by drying.
[0094] dry Drying in the first drying zone The coating film for the coating layer is dried to form a coating layer on at least one surface of a porous substrate, thereby manufacturing a diaphragm.
[0095] Drying includes drying the coating film by passing a laminate of a porous substrate and a coating film for the coating layer through a first drying zone.
[0096] The first drying zone is the area where the coating film used for the coating layer is dried for the first time. In the first drying zone, although relatively little solvent in the coating film used for the coating layer evaporates, it can promote phase separation between the filler and the binder in the coating film used for the coating layer.
[0097] The first drying zone has a dew point of 10°C to 25°C and a relative humidity of 20% to 70%. When the first drying zone meets both the above-mentioned dew point and relative humidity, the above-mentioned pore size, porosity, and phase separation can be easily achieved. The dew point and relative humidity appropriately provide moist conditions during the drying of the coating film used for the coating layer, therefore, it is expected that the above-mentioned pore size, porosity, and phase separation will be easily achieved, but this disclosure is not limited thereto.
[0098] When the first drying zone has a dew point below 10°C, problems such as high permeability and high resistance may exist.
[0099] When the first drying zone has a dew point above 25°C, problems such as low substrate bonding strength and low adhesion may occur.
[0100] When the first drying zone has a relative humidity of less than 20%, problems such as high air permeability and high resistance may occur.
[0101] When the first drying zone has a relative humidity greater than 70%, problems such as low substrate bonding strength and low adhesion may occur.
[0102] In one example, the first drying zone may have a dew point of 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, or 10°C to 20°C (e.g., 10°C to 18°C or 12°C to 18°C).
[0103] In one example, the first drying zone may have a relative humidity of 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 20% to 60% (e.g., 20% to 50% or 25% to 45%).
[0104] The dew point and relative humidity of the first dry zone can be controlled by an air handling unit (AHU) and an outdoor air control unit (OAC) connected to the first dry zone. The AHU and OAC can control the dew point and relative humidity using temperature and relative humidity controls known to those skilled in the art.
[0105] Here, "dew point" and "relative humidity" can be measured in the first dry zone using typical methods. Dew point is measured according to ASTM D1142 standard. Relative humidity (the ratio of actual water vapor content to saturated or maximum water vapor content (%)) is measured using a hygrometer or dew point hydrometer.
[0106] The first drying zone can have a concentration of 10g / m³. 3 Up to 35g / m 3The moisture content. Within the above range, the aforementioned pore size, porosity, and phase separation can be easily achieved. For example, the first drying zone can have a moisture content of 10 g / m³. 3 11g / m 3 12g / m 3 13g / m 3 14g / m 3 15g / m 3 16g / m 3 17g / m 3 18g / m 3 19g / m 3 20g / m 3 21g / m 3 22g / m 3 23g / m 3 24g / m 3 25g / m 3 26g / m 3 27g / m 3 28g / m 3 29g / m 3 30g / m 3 31g / m 3 32g / m 3 33g / m 3 34g / m 3 35g / m 3 10g / m 3 Up to 25g / m 3 10g / m 3 Up to 20g / m 3 Or 15g / m 3 Up to 20g / m 3 The moisture content.
[0107] Here, "moisture content" can be measured by reverse calculation using the following equation: Relative humidity = Actual weight absolute humidity (i.e., moisture content) / Saturated weight absolute humidity at a given temperature Saturated absolute humidity at dew point = actual absolute humidity (i.e., moisture content).
[0108] The first drying zone can have an internal temperature of 40°C to 100°C (e.g., 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 50°C to 80°C, 50°C to 70°C, 50°C to 60°C, or 60°C to 65°C). Within these ranges, the coating film used for the coating layer can be easily dried.
[0109] In the first drying zone, the laminate of the coating film and the porous substrate for the coating layer can be moved at a linear velocity of 20 meters per minute (mpm) to 150 mpm (e.g., 20 mpm, 25 mpm, 30 mpm, 35 mpm, 40 mpm, 45 mpm, 50 mpm, 55 mpm, 60 mpm, 65 mpm, 70 mpm, 75 mpm, 80 mpm, 85 mpm, 90 mpm, 95 mpm, 100 mpm, 105 mpm, 110 mpm, 115 mpm, 120 mpm, 125 mpm, 130 mpm, 135 mpm, 140 mpm, 145 mpm, 150 mpm, 20 mpm to 120 mpm or 60 mpm to 80 mpm). Within this range, the coating film for the coating layer can be easily dried.
[0110] Additional drying Drying may also include drying the coating film for the coating layer in an additional drying zone besides the first drying zone. In the additional drying zone, the solvent in the coating film for the coating layer can evaporate to remove the solvent from the coating layer and increase the strength of the coating layer.
[0111] The number of additional drying zones can be two or more (e.g., four or more).
[0112] In one example, the additional drying area may include a second drying area connected to the first drying area, a third drying area connected to the second drying area, a fourth drying area connected to the third drying area, and a fifth drying area connected to the fourth drying area.
[0113] The drying temperatures in the second, third, fourth, and fifth drying zones can be controlled according to the boiling point of the solvent included in the composition used for the coating layer. For example, the drying temperatures in the second, third, fourth, and fifth drying zones can be the same or different, and can be, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 40°C to 100°C, or 50°C to 80°C.
[0114] In the following, a separator for a rechargeable battery according to an example embodiment is described.
[0115] A separator for a rechargeable battery includes a porous substrate and a coating layer laminated on at least one surface of the porous substrate, the coating layer including an adhesive and a filler.
[0116] The porous substrate, binder, and filler are essentially the same as described above.
[0117] The coating has an average pore size greater than 0 nm and 50 nm or smaller (e.g., an average pore size greater than 10 nm and 50 nm or smaller, or an average pore size greater than 20 nm and 40 nm or smaller).
[0118] Within the above average pore size range, the membrane's permeability is prevented from increasing, and its surface roughness is low, thus enhancing battery safety. For example, the coating layer can have an average pore size of 5nm to 50nm, 10nm to 50nm, or 20nm to 40nm.
[0119] In one example, the coating may have a surface roughness Ra of 0.15 μm or less (e.g., 0.01 μm to 0.15 μm, 0.05 μm to 0.15 μm, or 0.1 μm to 0.15 μm). Within these ranges, battery safety can be enhanced.
[0120] In one example, the separator may have a permeability of 180 sec / 100 cc or less (e.g., 140 sec / 100 cc or less). Within this range, an increase in resistance can be prevented or avoided during battery operation.
[0121] The coating can have a thickness of 0.5 μm to 3.0 μm (e.g., 0.5 μm to 1.5 μm). Within this range, the coating can be used for a diaphragm.
[0122] Within a certain range of membrane resistance, battery life can be improved without reducing battery capacity. For example, the separator can have a membrane resistance of about 1 Ω or less (e.g., 0.8 Ω or less).
[0123] Figure 3 This is a cross-sectional view of a separator for a rechargeable battery according to an example embodiment.
[0124] Reference Figure 3 The separator for a rechargeable battery includes a porous substrate 1 and a coating layer 2 laminated on one surface of the porous substrate 1. The coating layer 2 includes a filler 3 and a binder 4. In the coating layer 2, a large amount of binder 4 may be present away from the porous substrate 1, and a relatively small amount of binder 4 may be present close to the porous substrate 1. Because a relatively large amount of binder 4 is located at the surface of the coating layer 2, the binder 4 can be separated from the filler 3.
[0125] Therefore, both the dry adhesion and wet adhesion of the diaphragm can be increased.
[0126] In one example, the diaphragm may have a dry adhesion force of 1.5 gf / mm or greater (e.g., 1.5 gf / mm to 3 gf / mm) and a wet adhesion force of 0.5 gf / mm or greater (e.g., 0.5 gf / mm to 2.5 gf / mm).
[0127] In one example, the separator can be manufactured using a method for manufacturing a separator for a rechargeable battery according to an example embodiment.
[0128] Rechargeable lithium batteries According to one example embodiment, a rechargeable lithium battery includes: a separator for the rechargeable lithium battery; a positive electrode; and a negative electrode.
[0129] The separator used in rechargeable lithium batteries is described above. The separator for rechargeable lithium batteries can be located between the positive and negative electrodes.
[0130] positive electrode The positive electrode for a rechargeable lithium battery may include a current collector and a layer of positive electrode active material on the current collector. The positive electrode active material layer may include positive electrode active material and may also include a binder and / or conductive material. For example, the positive electrode may also include additives that can constitute a sacrificial positive electrode.
[0131] Positive electrode active material The positive electrode active material may include compounds capable of inserting and deintercalating lithium (lithium-intercalating compounds). For example, at least one of a composite oxide of lithium and a metal (such as or including at least one of cobalt, manganese, nickel and combinations thereof) may be used.
[0132] The composite oxide can be or includes lithium transition metal composite oxides. Examples of composite oxides may include at least one of lithium nickel oxides, lithium cobalt oxides, lithium manganese oxides, lithium iron phosphate compounds, cobalt-free lithium nickel manganese oxides, or combinations thereof.
[0133] As an example, the following compounds, represented by any of the following chemical formulas, can be used. Li a A 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, and 0<α<2); Li a Ni 1-b-c Mn b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, and 0<α<2); Li a Ni b Co c L 1 d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0≤e≤0.1); Li a NiG b O2 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG b O2 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn 1-b G b O2 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn2G b O4 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn 1-g G g PO4 (0.90≤a≤1.8 and 0≤g≤0.5); Li (3-f) Fe2(PO4)3 (0≤f≤2); or Li a FePO4 (0.90≤a≤1.8).
[0134] In the above chemical formulas, A is or includes at least one of Ni, Co, Mn, or combinations thereof; X is or includes at least one of Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements, or combinations thereof; D is or includes at least one of O, F, S, P, or combinations thereof; G is or includes Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or combinations thereof; and L 1 It may be or include at least one of Mn, Al, or combinations thereof.
[0135] The positive electrode active material can be, or includes, for example, a high-nickel positive electrode active material, based on 100 mol% of metals other than lithium in a lithium transition metal complex oxide. The high-nickel positive electrode active material has a nickel content of greater than or equal to about 80 mol%, greater than or equal to about 85 mol%, greater than or equal to about 90 mol%, greater than or equal to about 91 mol%, or greater than or equal to about 94 mol% and less than or equal to about 99 mol%. High-nickel positive electrode active materials can achieve high capacity and can be used in high-capacity, high-density rechargeable lithium batteries.
[0136] Based on a 100 wt% positive electrode active material layer, the amount of positive electrode active material can range from about 90 wt% to about 99.5 wt%. Based on a 100 wt% positive electrode active material layer, the amount of each of the binder and conductive material can each independently range from about 0.5 wt% to about 5 wt%.
[0137] The binder causes the positive electrode active material particles to adhere to each other and also causes the positive electrode active material to adhere to the current collector. As a non-limiting example, examples of binders may include at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers including ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, nylon, etc.
[0138] Conductive materials can impart conductivity (e.g., electrical conductivity) to electrodes. Any material that does not cause adverse chemical changes (e.g., does not cause undesirable chemical changes in rechargeable lithium batteries) and conducts electrons can be used in batteries. Examples of conductive materials can include: carbon-based materials, such as at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metallic materials, including at least one of copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fibers; conductive polymers, such as polyphenylene derivatives; or mixtures thereof.
[0139] Al can be used as a current collector, but current collectors are not limited to this.
[0140] negative electrode The negative electrode for a rechargeable lithium battery may include a current collector and a layer of negative electrode active material on the current collector. The negative electrode active material layer may include a negative electrode active material and may also include a binder and / or a conductive material (e.g., an electrically conductive material).
[0141] For example, the negative electrode active material layer may include a negative electrode active material in a range of about 90 wt% to about 99 wt%, a binder in a range of about 0.5 wt% to about 5 wt%, and a conductive material in a range of about 0 wt% to about 5 wt%.
[0142] Negative electrode active material The negative electrode active material may include at least one of a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.
[0143] The material capable of reversibly intercalating / deintercalating lithium ions may include a carbon-based negative electrode active material (for example, crystalline carbon, amorphous carbon, or a combination thereof as examples). The crystalline carbon may be graphite, such as natural graphite or artificial graphite that is amorphous, flaky, flake-like, spherical, or fibrous. The amorphous carbon may be or include at least one of soft carbon, hard carbon, a mesophase pitch carbonized product, calcined coke, and the like.
[0144] The lithium metal alloy includes an alloy of lithium and a metal such as at least one of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0145] The material capable of doping / dedoping lithium may be or include a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (0<x≤2), at least one of Si-Q alloy (wherein Q is or includes at least one of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element (excluding Si), a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and a combination thereof). The Sn-based negative electrode active material may include at least one of Sn, SnO₂, a Sn-based alloy, or a combination thereof.
[0146] The silicon-carbon composite may be or include a composite of silicon and amorphous carbon. According to an exemplary embodiment, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on surfaces of the silicon particles. For example, the silicon-carbon composite may include secondary particles (core) assembled from primary silicon particles and an amorphous carbon coating layer (shell) on surfaces of the secondary particles. The amorphous carbon may also be present between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0147] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core containing crystalline carbon and silicon particles, and an amorphous carbon coating layer on a surface of the core.
[0148] Si-based or Sn-based negative electrode active materials can be used in combination with carbon-based negative electrode active materials.
[0149] The binder enables the negative electrode active material particles to adhere to each other and to adhere the negative electrode active material to the current collector. The binder may include non-aqueous binders, aqueous binders, dry binders, or combinations thereof.
[0150] Non-aqueous adhesives may include at least one of polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.
[0151] The waterborne adhesive may be or include at least one of styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0152] When an aqueous binder is used as the negative electrode binder, it may also include a cellulose compound capable of imparting viscosity. The cellulose compound may include at least one of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or an alkali metal salt thereof. The alkali metal may include at least one of Na, K, or Li.
[0153] Dry adhesives can be or include polymeric materials capable of being fibrous. For example, dry adhesives can be or include at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.
[0154] Conductive materials can impart conductivity (e.g., electrical conductivity) to electrodes. Any material that does not cause adverse chemical changes (e.g., does not cause undesirable chemical changes in rechargeable lithium batteries) and conducts electrons can be used in the battery. Non-limiting examples of conductive materials may include: carbon-based materials, such as at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metallic materials, including at least one of copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fibers; conductive polymers, such as polyphenylene derivatives; or mixtures thereof.
[0155] The negative electrode current collector may include at least one of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0156] Rechargeable lithium batteries may also include an electrolyte.
[0157] electrolyte Electrolytes used in rechargeable lithium batteries may include non-aqueous organic solvents and lithium salts.
[0158] Non-aqueous organic solvents can serve as a medium for transporting ions that participate in the electrochemical reactions of a battery.
[0159] Non-aqueous organic solvents may be or include at least one of carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents, or combinations thereof.
[0160] Carbonate solvents may include at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC).
[0161] Ester solvents may include at least one of the following: methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, caprolactone, etc.
[0162] Ether solvents may include at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Additionally, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc. Aprotic solvents may include at least one of the following: nitriles, such as R-CN (wherein R is a C2 to C20 straight-chain, branched, or cyclic hydrocarbon group, and may include double bonds, aromatic rings, or ether bonds, etc.); amides, such as dimethylformamide; dioxolane, such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane, etc.
[0163] Non-aqueous organic solvents can be used alone or in combination of two or more solvents.
[0164] In addition, when using carbonate solvents, cyclic carbonates and chain carbonates can be mixed together, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio ranging from about 1:1 to about 1:9.
[0165] Lithium salts dissolved in organic solvents supply lithium ions in batteries, enabling rechargeable lithium batteries to operate fundamentally and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, and LiN(C x F 2x+1 SO2)(C y F 2y+1 At least one of the following: (SO2) (where x and y are integers in the range of 1 to 20), lithium trifluoromethane sulfonate, lithium tetrafluoroethane sulfonate, lithium difluoro(oxalate)borate (LiDFOB), lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).
[0166] Rechargeable lithium batteries can be classified according to their shape, such as cylindrical, prismatic, pouch, or coin-shaped batteries.
[0167] Figures 4 to 7 This is a schematic diagram illustrating a rechargeable lithium battery according to an example embodiment. Figure 4 A cylindrical battery is shown. Figure 5 A prismatic battery is shown. Figure 6 and Figure 7 A pouch-type battery is shown. (See reference) Figures 4 to 7 The rechargeable lithium battery 100 may include an electrode assembly 40 and a housing 50. The electrode assembly 40 includes a separator 30 between a positive electrode 10 and a negative electrode 20, and is included in the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown). Figure 4 As shown, the rechargeable lithium battery 100 may include a sealing member 60 of a sealed housing 50. Figure 5 In this context, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12 connected to the positive electrode lead connector 11, a negative electrode lead connector 21, and a negative electrode terminal 22 connected to the negative electrode lead connector 21. For example... Figure 6 and Figure 7 As shown, the rechargeable lithium battery 100 may include Figure 7 The electrode terminal 70 shown, or for example Figure 6 The positive electrode terminal 71 and negative electrode terminal 72 shown form an electrical path for guiding the current formed in the electrode assembly 40 to the outside of the rechargeable lithium battery 100.
[0168] As a non-limiting example, the rechargeable lithium battery according to the example embodiment can be used in, for example, automobiles, mobile phones and / or various types of electronic devices.
[0169] Figure 10 This is a flowchart illustrating a method for manufacturing a separator for a rechargeable battery according to an example embodiment. Figure 10 In method 1000, operations 1010 and 1020 are included. Operation 1010 includes applying a composition comprising an adhesive, a solvent, and a filler to at least one surface of a porous substrate to form a coating film for the coating layer. In another example, the adhesive comprises an organic adhesive. For example, an organic adhesive includes a fluorinated adhesive having a carboxylic acid group or a hydroxyl group. In another example, a fluorinated adhesive having a carboxylic acid group or a hydroxyl group includes a polyvinylidene fluoride (PVDF) adhesive having a carboxylic acid group or a hydroxyl group. In yet another example, the solvent has a boiling point of about 80°C or lower. For example, the solvent includes at least one of acetone, ethanol, methyl ethyl ketone, ethyl isobutyl ketone, tetrahydrofuran, dimethylformaldehyde, cyclohexane, and mixtures thereof. In another example, the filler comprises alumina having an average particle size D50 of about 0.5 μm or less. In yet another example, the adhesive and filler are included in the composition for the coating layer in a weight ratio ranging from about 1:10 to about 1:50. For example, the solvent is included in an amount ranging from about 100 parts by weight to about 500 parts by weight relative to 100 parts by weight of the adhesive.
[0170] Operation 1020 includes drying the coated membrane to manufacture a separator for a rechargeable battery. For example, drying includes drying the coated membrane in a first drying zone having a dew point in the range of about 10°C to about 25°C and a relative humidity in the range of about 20% to about 70%. For example, the laminate of the coated membrane and the porous substrate for the coating layer moves in the first drying zone at a speed in the range of about 50 mpm to about 150 mpm. In another example, the first drying zone has a dew point in the range of about 10 g / m³. 3 Approximately 35g / m 3 The moisture content is within a range of approximately 50°C to approximately 100°C. In another example, drying includes drying the coated film in an additional drying zone in addition to the first drying zone.
[0171] Examples and comparative examples of this disclosure are described below. However, the following examples are given only to illustrate the disclosure, and the disclosure is not limited to these examples.
[0172] Example 1 Alumina (particle size D50: 200nm) was used as the filler.
[0173] A polyvinylidene fluoride-hexafluoropropylene binder 75130 (weight average molecular weight: 1,300,000 g / mol, polyvinylidene fluoride:hexafluoropropylene molar ratio: 98:2, including acrylic acid as a monomer, glass transition temperature: -30℃, melting point: 154℃, crystallinity: 53%) with carboxylic acid groups was used as a binder.
[0174] The filler and a polyvinylidene fluoride-hexafluoropropylene binder with carboxylic acid groups were mixed in acetone and stirred to prepare a composition for coating.
[0175] The composition for use in the coating layer includes a polyvinylidene fluoride-hexafluoropropylene binder and a filler in a weight ratio of 1:20. The composition for use in the coating layer includes acetone in an amount of 300 parts by weight relative to 100 parts by weight of the polyvinylidene fluoride-hexafluoropropylene binder.
[0176] The composition for coating is applied to a surface of a polyethylene film (thickness: 5.5 μm, commercially available from CZMZ, air permeability: 110 sec / 100 cc, puncture strength: 360 kgf) serving as a porous substrate to prepare a coated film (thickness: 20 μm) for coating.
[0177] The porous substrate and the laminate of the coating film for the coating layer are dried by passing them through the first drying zone shown in Table 1 below.
[0178] Then, the laminate is sequentially passed through the second drying zone (drying temperature: 50°C, drying time: 2 minutes), the third drying zone (drying temperature: 50°C, drying time: 2 minutes), the fourth drying zone (drying temperature: 50°C, drying time: 2 minutes), and the fifth drying zone (drying temperature: 50°C, drying time: 2 minutes) to manufacture a diaphragm.
[0179] Example 2 and Example 3 Except for changing the dew point, relative humidity, and moisture content of the first dry zone in Example 1 as shown in Table 1 below, the diaphragm is manufactured in the same manner as in Example 1.
[0180] Comparison Examples 1 through 3 and Comparison Example 6 Except for changing the dew point, relative humidity, and moisture content of the first dry zone in Example 1 as shown in Table 1 below, the diaphragm is manufactured in the same manner as in Example 1.
[0181] Compare Example 4 and Compare Example 5 Except that the first dry zone is not subjected to humid conditions, the diaphragm is manufactured in the same manner as in Example 1.
[0182] The physical properties of the diaphragms manufactured in the following evaluation and comparative examples are shown below.
[0183] Breathability (unit: sec / 100cc) The permeability is determined by measuring the time (in seconds) it takes for 100cc of air to pass through the diaphragm using a measuring device (preferably a digital Oken type air permeability tester) (commercially available from ASAHI SEIKO Co.Ltd. EG01-55-1MR).
[0184] Air permeability measurement device setup: Measured pressure: 0.5 kg / cm 2 Cylinder pressure: 2.5 kg / cm² 2 Set time: 10 seconds Membrane resistance (unit: Ω) Membrane resistance was evaluated using electrochemical impedance spectroscopy (EIS). Separators fabricated in the example and comparative examples were impregnated with electrolyte (1.5 M LiPF6 dissolved in a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 2:1:7), mounted onto aluminum foil electrodes with leaded terminals, and sealed in an aluminum cask to fabricate test cells. The resistance (Ω) of the test cells was measured at 20°C using alternating current (AC) impedance spectroscopy (measurement frequency: 100 kHz).
[0185] Dry adhesion (unit: gf / mm) Samples were prepared by cutting the separators for rechargeable lithium batteries according to the example and comparative examples into 3cm × 8cm dimensions.
[0186] A negative electrode active material slurry was prepared by mixing 97.4 wt% of artificial graphite as the negative electrode active material, 1.0 wt% of carboxymethyl cellulose, 1.5 wt% of styrene-butadiene rubber, and 0.1 wt% of carbon nanotubes as the conductive material. The prepared negative electrode slurry was coated onto copper foil, dried, and rolled to manufacture the negative electrode.
[0187] The negative electrode and diaphragm were stacked and held at 40°C with a 50 kg load for 2 hours. Afterward, the negative electrode and diaphragm were separated by approximately 10 mm to 20 mm and fixed to the lower and upper clamps respectively, with a 20 mm gap between the clamps. The diaphragm was subjected to a tensile test at a speed of 100 mm / min in a direction at 180° to the negative electrode. The force required to peel 40 mm was measured three times, and the arithmetic mean was obtained. The adhesion force was measured using a universal testing machine (UTM).
[0188] Adhesive Distribution Index (FT-IR): The binder distribution index (FT-IR) was measured using the PMI method.
[0189] Wet adhesion (unit: gf / mm) Samples were prepared by cutting the separators for rechargeable lithium batteries according to the example and comparative examples into 3cm × 8cm dimensions.
[0190] A positive electrode slurry was prepared by mixing 97 wt% lithium nickel cobalt aluminum oxide as the active material for the positive electrode, 1.5 wt% carbon nanotubes as the conductive material, and 1.5 wt% polyvinylidene fluoride as the binder, and water was added. The prepared positive electrode slurry was coated onto aluminum foil, dried, and rolled to manufacture the positive electrode.
[0191] A negative electrode active material slurry was prepared by mixing 97.4 wt% of artificial graphite as the negative electrode active material, 1.0 wt% of carboxymethyl cellulose, 1.5 wt% of styrene-butadiene rubber, and 0.1 wt% of carbon nanotubes as the conductive material. The prepared negative electrode slurry was coated onto copper foil, dried, and rolled to manufacture the negative electrode.
[0192] A sample was inserted between the positive and negative electrodes, and the positive electrode-sample-negative electrode laminate was placed in a bag. 2.5 g of electrolyte (in which 1.5 M LiPF6 was dissolved in ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate (volume ratio 30:50:20)) was injected, the bag was sealed, and it was allowed to stand at 25°C for 12 hours. Afterward, the bag was placed in a chamber at 50°C under a pressure of 200 kgf for 2 hours. The diaphragm was separated from the negative electrode plate by approximately 10 mm to 20 mm, and the diaphragm and negative electrode plate were fixed to the upper and lower clamps, respectively, with a 20 mm gap between the clamps. The diaphragm was then subjected to a tensile test involving peeling at 180° to the negative electrode plate. In this case, the peeling speed was 20 mm / min, and the force required to peel 40 mm was measured three times after the peeling began, and the average value was obtained. The average value was calculated from the measurements. The adhesion force was measured using a UTM.
[0193] Average pore size (unit: nm) The average aperture was measured using the PMI method.
[0194] Porosity (unit: %) Porosity was measured using the PMI method.
[0195] Surface roughness Ra (unit: μm) The surface of the porous membrane was measured using a microscope commercially available from Olympus Corporation. The arithmetic mean roughness (Ra) was obtained from the arithmetic mean of the absolute vertical coordinates over the sampling length.
[0196] SEM results The surfaces of the coatings according to Example 1 and Comparative Example 4 were measured using a scanning electron microscope (SEM). Figure 8 The SEM results for Example 1 are shown. Figure 9 The SEM results for comparison with Example 4 are shown.
[0197] Table 1:
[0198] As shown in Table 1, the example membrane has a small average pore size, high porosity, and phase separation between the binder and the filler.
[0199] According to one example embodiment, the separator for a rechargeable battery enhances battery safety by having a small average pore size and high porosity.
[0200] According to one example embodiment, the separator for a rechargeable battery has high adhesion to the electrodes, preventing or inhibiting battery deformation during charging and discharging, and providing improved short-circuit defects and overcharging effects by including a coating layer with phase separation between the binder and the filler.
[0201] Example embodiments of this disclosure have been described, but this disclosure is not limited thereto. Various modifications can be made within the scope of the claims, the detailed description of this disclosure, and the accompanying drawings, and such modifications are also included within the scope of this disclosure.
Claims
1. A method for manufacturing a separator for a rechargeable battery, the method comprising the steps of: A composition for coating, comprising an adhesive, a solvent, and a filler, is applied to at least one surface of a porous substrate to form a coating film for coating. as well as The coated film is dried to manufacture the separator for the rechargeable battery. The drying process includes drying the coating film in a first drying zone, wherein the first drying zone has a dew point in the range of 10°C to 25°C and a relative humidity in the range of 20% to 70%.
2. The method according to claim 1, wherein, The first drying zone has a concentration of 10 g / m 3 Up to 35g / m 3 The moisture content within the range of 50°C to 100°C and the internal temperature within the range of 50°C to 100°C.
3. The method according to claim 1, wherein, The laminate of the coating film for the coating layer and the porous substrate moves in the first drying zone at a speed ranging from 50 mpm to 150 mpm.
4. The method according to claim 1, wherein, Drying also includes drying the coating film for the coating layer in an additional drying zone in addition to the first drying zone.
5. The method according to claim 1, wherein, The adhesive includes organic adhesives.
6. The method according to claim 5, wherein, The organic adhesive includes fluorinated adhesives having carboxylic acid groups or hydroxyl groups.
7. The method according to claim 6, wherein, The fluorinated adhesives having carboxylic acid groups or hydroxyl groups include polyvinylidene fluoride adhesives having carboxylic acid groups or hydroxyl groups.
8. The method according to claim 1, wherein, The solvent has a boiling point of 80°C or lower.
9. The method according to claim 8, wherein, The solvent includes at least one of acetone, ethanol, methyl ethyl ketone, ethyl isobutyl ketone, tetrahydrofuran, dimethylformaldehyde, cyclohexane, and mixtures thereof.
10. The method according to claim 1, wherein, The filler comprises alumina with an average particle size D50 of 0.5 μm or less.
11. The method according to claim 1, wherein, The adhesive and the filler are included in the composition for coating in a weight ratio ranging from 1:10 to 1:
50.
12. The method according to claim 11, wherein, The solvent is included in the range of 100 to 500 parts by weight relative to 100 parts by weight of the adhesive.
13. A separator for a rechargeable battery, the separator comprising: Porous substrate; and a coating layer, laminated on at least one surface of the porous substrate, The coating layer includes an adhesive and a filler, and has an average pore size greater than 0 nm and 50 nm or smaller, and a film resistance of 1 Ω or smaller.
14. The diaphragm according to claim 13, wherein: The coating layer has a surface roughness Ra of 0.15 μm or less, and The diaphragm has an air permeability of 180 sec / 100 cc or less.
15. The diaphragm according to claim 13, wherein: The adhesive includes fluorinated adhesives, and The filler comprises alumina with an average particle size D50 of 0.5 μm or less.
16. The diaphragm according to claim 13, wherein, The adhesive and the filler are included in the coating in a weight ratio ranging from 1:10 to 1:
50.
17. The diaphragm according to claim 13, wherein, The separator for the rechargeable battery is manufactured by the method according to any one of claims 1 to 12.
18. A rechargeable battery, said rechargeable battery comprising: Positive electrode; negative electrode; as well as The diaphragm according to any one of claims 13 to 17 is located between the positive electrode and the negative electrode.
Citation Information
Patent Citations
SAR data learning apparatus and target classification apparatus using the same
KR1020250057450A